Thermal Comfort Analysis in the Classrooms of the Faculty of Islamic Education and Teacher Training at UIN Raden Intan Lampung - Panggabean Siti Munawarah; Rizaini Mutiara Arda; Kuswanto Eko; Ardianti Indah Marlina; Andandaningrum Della (E3S Web of Conferences, 2024)
Thermal comfort in the classroom environment serves as a crucial factor influencing the quality of the teaching and learning process. Preliminary research reveals that a significant number of students at UIN Raden Intan Lampung have expressed complaints regarding excessively hot classroom conditions, lacking adequacy in creating comfort. The primary objective of this study is to assess the extent to which the level of thermal comfort can be achieved in the classrooms within the Faculty of Islamic Education at UIN Raden Intan Lampung. The research methodology applied in this study is qualitative and descriptive, with a focus on variables such as temperature, humidity, wind speed, and lighting levels. The purposively selected sample indicates that the classroom conditions in the Faculty of Islamic Education at UIN Raden Intan Lampung have not yet met the desired standards of thermal comfort.